جماليات العمارة الطينية في المناطق الجافة والقاحلة - الحسيني, عبد الحكيم (Latakia University Journal -Engineering Sciences Series, 2019)
تفيد المكتشفات الأثرية أن العمارة الطينية ظهرت في منطقتنا منذ حوالي عشرة آلاف سنة خلت. ومنذ ذلك الوقت ترتبط هذه العمارة بالمكان، وهي توفر الأمان والراحة في البيئات الجافة. تعتمد تقنياتها على ما يتوافر من مواد بسيطة كالطين والماء وأحيانا بعض الأخشاب. وتدل التجارب على أن هذه المواد توفر الطاقة المستخدمة في التصنيع، وتساعد على توفير المسكن للتجمعات البشرية في المناطق الصحراوية والجافة، وتقيها من المؤثرات القاسية لأشعة الشمس ودرجات الحرارة المرتفعة. ولها تقنيات خاصة عملية وجمالية. ولها ثقافة إنسانية قديمة تعتمد على العناصر الزخرفية اللدائنية النحتية بين الغائر والنافر، وكذلك اللون والتشكيل، إلى جانب ما يتوافر من نباتات ممكنة في البيئة المحيطة. 10 thousand years ago, earth architecture existed in our region as archeological discoveries reveal. Earth architecture is tied in with place and it serves as a shelter and offers safety for human beings in dry environments. Techniques used in earth architecture are often based on simple materials like clay, water and wood. Evidences show that such materials need less power to be ready for getting into the constructing process. Earth architecture is mainly used for residential purposes. In deserts, earth architecture protects the human communities from high level of temperature and solar radiations. Earth architecture utilizes unique practical and aesthetical techniques. It has got an ancient humanistic culture. This culture is well-crystallized in ornamental, chromatic and compositional features of earth architecture buildings. These buildings also have carving aspects varies from Relief to Pararelief. Moreover, they are decorated by botanic elements available in arid lands.